2008
DOI: 10.1089/cmb.2007.0183
|View full text |Cite
|
Sign up to set email alerts
|

Shift-Invariant Adaptive Double Threading: Learning MHC II–Peptide Binding

Abstract: The major histocompatibility complex (MHC) plays important roles in the workings of the human immune system. Specificity of MHC binding to peptide fragments from cellular and pathogens' proteins has been found to correlate with disease outcome and pathogen or cancer evolution. In this paper we propose a novel approach to predicting binding configurations and energies for MHC class II molecules, whose epitopes are generally predicted less well than the MHC I epitopes due in part to larger variation in bound pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Using thousands of peptide-binding data points, several predictors have been developed and benchmarked (for review, see Nielsen et al 2010b). One very important subset of these predictors consists of the so-called pan-specific methods that are capable of obtaining accurate predictions for molecules with limited or no binding data (Nielsen et al 2008, 2010a; Zaitlen et al 2008; Zhang et al 2005). For MHC class I prediction, it has been demonstrated that a pan-specific approach can benefit from being trained on cross-loci, and even cross-species, data.…”
Section: Introductionmentioning
confidence: 99%
“…Using thousands of peptide-binding data points, several predictors have been developed and benchmarked (for review, see Nielsen et al 2010b). One very important subset of these predictors consists of the so-called pan-specific methods that are capable of obtaining accurate predictions for molecules with limited or no binding data (Nielsen et al 2008, 2010a; Zaitlen et al 2008; Zhang et al 2005). For MHC class I prediction, it has been demonstrated that a pan-specific approach can benefit from being trained on cross-loci, and even cross-species, data.…”
Section: Introductionmentioning
confidence: 99%
“…These PSSMs are derived from 11 HLA DRB alleles: DRB1*01:01, DRB1*03:01, DRB1*04:01, DRB1*04:02, DRB1*04:04, DRB*07:01, DRB1*08:01, DRB1*11:01, DRB1*13:02, DRB1*15:01 and DRB5*01:01 (the alleles in this paper are represented in current HLA allele nomenclature [24]). There are other five pan-specific methods: MHCIIMulti [25], NetMHCIIpan-1.0 [26], NetMHCIIpan-2.0 [27], MultiRTA [28] and SIADT (Shift Invariant Adaptive Double Threading) [29]. MHCIIMulti is a kernel based method, in which the binding specificity of a target MHC with no binding data can be predicted by using binding data of related MHC alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of those methods was typically done using existing structures or a small dataset of known binders and none of them currently provides a public web server. Finally, so-called pan-specific MHC binding predictors have been developed in recent years integrating structural information with experimental peptide binding data allowing for generalization of binding predictions to MHC molecules characterized with few or even no peptide binding data [12], [13], [14], [15], [16], [17] [18].…”
Section: Introductionmentioning
confidence: 99%